Tingkat Rasa Percaya Diri Siswa pada Pembelajaran Senam Lantai - Egi Aldi Reza; Muhammad Mury Syafei; Irfan Zinat Achmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to determine the level of self-confidence in learning floor exercise for seventh grade students of SMP Negeri 1 Pebayuran, Bekasi Regency. This research is quantitative descriptive. The method used is a survey and data collection techniques using a questionnaire or questionnaire. The population was 273 students with a sample of 74 students using the quota sample. The instrument uses a closed questionnaire included in the rating scale questionnaire. Using a Likert Scale. In the overall research results show the level of front roll confidence in learning floor gymnastics with a percentage of 50%. In conclusion, the level of self-confidence is in the unfavorable category. Keywords : Level Of Self Confidence, Gymnastics.